Efektifitas Pengurangan Paramater BOD COD Menggunakan Moving Bed Biofilm Reaktor - Muliyadi Muliyadi; Idayani Sangadjisowohy; Sumiati Tomia; Herwin Hi Adam (Poltekkes Kemenkes Padang, 2026)
Domestic wastewater with high organic loads exceeding the Indonesian regulatory standards (Permen LHK No. 68/2016) requires an effective and economical treatment system prior to discharge. The utilization of plastic waste as biofilm carrier media in a Moving Bed Biofilm Reactor (MBBR) represents an innovative and environmentally friendly alternative. This study aimed to evaluate the performance of an aerobic MBBR using polypropylene (PP) bottle caps as carrier media in reducing BOD and COD, while analyzing biofilm dynamics and operational conditions. A laboratory-scale experimental approach was conducted over 31 days using an 80 L working volume reactor containing 500 media units with a total surface area of 1.413 m². Temperature, pH, BOD, and COD were monitored periodically. Results indicated stable operating conditions at an average temperature of 29.2°C and pH 7.2, with optimal biofilm development observed by day 30. BOD decreased from 193 mg/L to 31–33 mg/L and COD from 343 mg/L to 95–97 mg/L, achieving 73% COD removal efficiency. It is concluded that the aerobic MBBR with PP bottle cap media effectively reduces organic loads and shows strong potential as a low-cost wastewater treatment technology.